2016
DOI: 10.1088/1748-9326/11/9/094020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of charcoal production on forest degradation: a case study in Tete, Mozambique

Abstract: Charcoal production for urban energy consumption is a main driver of forest degradation in sub Saharan Africa. Urban growth projections for the continent suggest that the relevance of this process will increase in the coming decades. Forest degradation associated to charcoal production is difficult to monitor and commonly overlooked and underrepresented in forest cover change and carbon emission estimates. We use a multitemporal dataset of very high-resolution remote sensing images to map kiln locations in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 27 publications
6
80
1
2
Order By: Relevance
“…Our analysis indicates that charcoal production constitutes and independent driver of forest degradation, not associated with other processes of forest cover change. While this finding is supported by previous studies in the region (Sedano et al 2016), this production pattern may not be uniform across SSA. Additional research is still required in other woodlands of the region with higher precipitation and more fertile soils where charcoal production could be a secondary product of agricultural expansion.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our analysis indicates that charcoal production constitutes and independent driver of forest degradation, not associated with other processes of forest cover change. While this finding is supported by previous studies in the region (Sedano et al 2016), this production pattern may not be uniform across SSA. Additional research is still required in other woodlands of the region with higher precipitation and more fertile soils where charcoal production could be a secondary product of agricultural expansion.…”
Section: Discussionsupporting
confidence: 59%
“…In this case study, the impact of forest degradation in the Mabalane district is comparable to forest loss in the entire southern Mozambique, making charcoal production the main contributor to forest cover change. Sedano et al (2016) reported that charcoal production could extract up to 80% of AGB in tropical dry woodlands of central Mozambique. If similar numbers are considered in this context, gross carbon emissions from forest degradation would, despite just partially removing AGB, be comparable to those of deforestation in southern Mozambique.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of agriculture and urbanization are drivers as well. This is supported by studies that have attributed deforestation to charcoal production in Sub-Saharan Africa [3] [5] [6].…”
Section: Land Use Driversmentioning
confidence: 56%
“…It is estimated that between 100,000 and 125,000 ha of forest is lost annually as a result of charcoal-burning in Tanzania (World Bank, 2009). Sedano et al (2016) found that the high demand for charcoal in urban areas is the main driver of forest degradation in most Sub-Saharan Africa. This evidence attests to charcoal-burning constituting a primary threat to the forest resources, which was contributed to the reduction of honey production in most beekeeping areas.…”
Section: Increased Charcoal-burningmentioning
confidence: 99%